Orthogonal Test Data Analysis on Visual Platform Based on C++ Builder - Jianhua Ren; Chuan Li; Zhengang Liang; Ziyong Zhai (Institute of Advanced Engineering and Science, 2013)
The design method of orthogonal test is commonly used in engineering test. It is very effective when many factors’ influences on one test .Orthogonal table experimental design is necessary to simplify the test procedure, to reduce the number of tests, and to improve test efficiency. By the orthogonal test, a level of each factor can be chosen to form the optimal production conditions. But in the current orthogonal experiment data analysis, we always adopt the manual calculation, and we will make big errors when we have a complex calculation. Therefore we consider the development by using computer programming of c++ computer Builder to solve this problem. As long as the programming completed, the test data can be input to calculation, analysis, and the visual interface, more intuitively and simply. DOI: http://dx.doi.org/10.11591/telkomnika.v11i8.3102